Non-symmetric single-molecule electric properties towards stochastic molecular computation. Issue 3 (4th May 2017) - Ogawa, Takuji
Abstract: Non-symmetric electric properties such as rectification, negative differential resistance, threshold gate, hysteresis effect, and integrated threshold gate are essential for realizing molecular brain computer, which are believed to withstand noise and fluctuations. Thus far, there is no fixed design principle for single-molecule electronic devices, mainly because the current–voltage ( I – V ) characteristics of such devices differ owing to differing conduction mechanisms. In the tunneling regime of the molecules, the I – V characteristics are essentially dependent on the density of states of the system, while in the hopping mechanisms, the molecules can be charged to change their electronic characteristics. To understand the principle, we have synthesized a series of molecules to study the electric properties of single molecules. Abstract : Non-linear electric properties such as rectification, negative differential resistance, threshold gate, hysteresis effect, and integrated threshold gate in single molecules which are essential to realize stochastic molecular computation are reviewed.